Interferon-induced pulmonary hypertension: an update. Issue 5 (September 2016) - Savale, Laurent; Chaumais, Marie-Camille; O'Connell, Caroline; Humbert, Marc; Sitbon, Olivier
Abstract : Purpose of review: Pulmonary adverse effects of interferon (IFN) therapies are rare but can be life threatening. This article proposes to review clinical and experimental data suggesting a causal link between interferon exposure and pulmonary arterial hypertension (PAH). Recent findings: Interferon has recently been added to the list of possible risk factors for PAH. This was justified by the reporting of many cases of pulmonary hypertension potentially associated with IFN-α or IFN-β exposure. Some of them were reversible after cessation of interferon exposure, especially in patients without concomitant risk factors for pulmonary hypertension. In contrast, it remains a challenge to definitively confirm the causal role of IFN-α in patients treated for hepatitis C viral infection because of frequent concomitant PAH risk factors such as portal hypertension and/or HIV infection. In these patients, temporal and clinical arguments suggest that interferon may potentially act as an additional trigger for PAH. Moreover, the information obtained from clinical experience with interferon therapy has been enriched by basic science research on this topic suggesting that interferon is involved in both human and experimental pulmonary hypertension. Summary: Many clinical and experimental data corroborate the link between interferon exposure and the risk to develop PAH.